BS EN 3660-005. Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Part 005. Cable outlet, style A, 90°, unsealed with clamp strain relief. Product standard (17th January 2020) - British Standards Institution,
No abstract available